Probing learners' conceptual understanding of oxidation and reduction (redox) reactions : a case study - Addam, Billey Bright (Rhodes University, Faculty of Education, Department of Education, 2004)
The new political dispensation in South Africa has seen a lot of changes taking place. The democratic wind, which has been blowing in all spheres of the political arena, could not leave out Education. This has led to the transformation in education and the revision of the curriculum guided by the Outcomes-Based Education philosophy (OBE). Thus, require education authorities as well as educators to look at education more comprehensively. The challenge posed to educators now is to develop tools and strategies that will make learning accessible to as many learners as possible and to teach for understanding and construction of knowledge. The principal objective of this study was to investigate the important role the learner's prior knowledge plays and the use of different tools and strategies in stimulating conceptual understanding and construction of knowledge of redox reactions. This was done using learners' own investigations, practical activities, teaching settings and a workshop. The findings show that the learners lacked organized and structured prior knowledge. Learners could not integrate prior experience with new experience. The main issue seems to be the failure of learners to relate classroom experience to everyday redox phenomena. Possible reasons are discussed with some implications for teaching redox. The study further postulates that to assist learners to develop conceptual understanding of redox reactions, different tools and strategies should be employed and teaching made relevant to real-life situations. In so doing, redox concepts would not be abstract to learners.
Keywords: Competency based education -- South Africa; Oxidation-reduction reaction -- Study and teaching; Science -- Study and teaching -- South Africa